Fresno’s BID for downtown revitalization: an analysis of a business improvement district - Kutz, Christopher (Kansas State University, 2017)
In the mid-20th century a migration took place taking residents of American downtowns to the newly-developed, master-planned suburbs. In the wake were abandoned urban cores that evolved into poorly-perceived conditions. One of the many responses to correct these deteriorating central districts was the establishment of Business Improvement Districts (BID), a public-private partnership that develops complementary services to what a city already provides and is paid for by assessments collected from property and business owners in a defined area. With more than 1,000 BIDs in existence in the United States as of 2010 (Becker, Grossman, Dos Santos, 2011), the concept has caught on as a tool utilized to bring downtowns back to life. However, despite the popularity of BIDs and their nearly 50-year existence as a planning tool, the question of how successful they are in improving the conditions of safety, cleanliness, and business growth in the districts over time needs continued analysis. This study gauges the impact of BIDs through a case study of Fresno, California and its BID, the Downtown Fresno Partnership. To measure how the Downtown Fresno Partnership has been successful or unsuccessful, interviews with Downtown Fresno stakeholders were conducted to measure the BID’s ability to change perceptions and advocate for the property owners in its boundary. Also, to measure further impacts, crime, property values and retail data was investigated. A perceived injection of new energy seems to exist in Downtown Fresno, as evidenced by the activity taking place and the change in perception of the area since the Downtown Fresno Partnership was formed in 2011. The BID has played a central role in instituting physical change to the space while it has been a strong advocate for its property owners. In its first five years of existence, the Downtown Fresno Partnership has proven to be necessary, but it is not sufficient on its own. From a planning standpoint, it is important to recognize that in order to revitalize, a community must first organize. In the case of Fresno, the BID provided an opportunity to collect formerly competing interests and put itself at the center of an underperforming downtown to alter the course towards a more vibrant and thriving area. It has established positive momentum down this path, and it is expected to be a strong voice for downtown in the future as others join in on the fully-experienced revitalized state of Downtown Fresno.
Keywords: Urban planning; Business Improvement District; Downtown revitalization